Bioinspired Trans‐Scale Functional Interface for Enhanced Enzymatic Dynamics and Ultrasensitive Detection of microRNA. (1st March 2018) - Ye, Lei; Yang, Fan; Ding, Yuanlin; Yu, Haibin; Yuan, Lin; Dai, Qi; Sun, Yujie; Wu, Xiaoxue; Xiang, Yang; Zhang, Guo‐Jun
Abstract: Protein interactions with specific nucleic acid sequences are crucial in cell growth. Inspired by such binding events that often occur at nanoscale biointerface, here a trans‐scale functional interface capable of considerably enhancing in vitro DNA‐enzyme interaction is reported. Using a screen‐printed electrode with nanoroughened carbon surface, the high‐curvature gold nanostructures in a single electrodeposition step can be programmed. In this process, a synergistic effect is found between nanoroughened carbon and polyelectrolyte multilayer enabling the formation of high‐stability and high‐curvature nanostructures. More importantly, these fractal nanostructures effectively overcome neighboring probes aggregation at high density and allow the probes to be more freely accessed by target molecules. As compared to its planar counterparts, this nanostructuring interface demonstrates faster enzymatic dynamics that enables ultrasensitive detection of microRNA with a detection limit of 35 × 10 −18 m . Such an efficient trans‐scale biosensing interface has also accurately differentiated the patients with rheumatic arthritis from the health ones, signifying its great potential in precision medicine. Abstract : Inspired by intracellular protein–nucleic acid binding events that often occur at nanoscale biointerface, here a high‐performance trans‐scale functional interface capable of considerably enhancing in vitro DNA‐enzyme interaction is reported. The high‐curvature nanostructuring surface affords high probe density and absolute molecular numbers, accelerates interfacial biomolecular diffusions, allows probe molecules to be easily accessible, and enables ultrasensitive detection of miRNA.